Pengembangan Lembar Kerja Peserta Didik Berbasis Kreativitas Materi Sifat-Sifat Bangun Datar: Development of Student Worksheets Based on Creativity on the Material of the Properties of Planar Shapes - Fatimaturradhu MR; Lailatun Nur Kamalia Siregar (ITScience (Information Technology and Science), 2024)
Education is a horizontal and important need for a better future. The transformation of education today has changed because education does not only transfer knowledge, nor is education centered only on teachers. Based on the results of the researcher's observations of the learning process carried out at SDN Alue Merbau, it is known that the mathematics learning process is still considered centered on teachers. Therefore, to improve the mathematics learning process at SDN Alue Merbau, variations and innovations in teaching materials are needed when compiling creativity-based LKPD. This type of research is research and development (Research and Development or R&D), which produces products in the form of creativity-based LKPD and is located at SDN Alue Merbau. The results of the study showed that the development of creativity-based LKPD on the material of the properties of flat shapes at SDN Alue Merbau was considered to have provided an alternative for teachers to improve the ability to solve mathematical problems experienced by students. The development of creativity-based LKPD on the material of the properties of flat shapes at SDN Alue Merbau has provided an alternative for teachers to improve the ability to solve mathematical problems experienced by students. This development research has produced creativity-based mathematics LKPD. Mathematics LKPD on the material of the properties of plane shapes has undergone validity testing by teachers as practitioners.